A case study analysis of the coach-athlete dyad in different age grade nonelite rugby union teams - Smith, K.; Burns, C.; O`Neill, C.; Quinn, N.; Duggan, J. D.; Winkelman, N.; Wilkie, M.; Coughlan, E. K. (International Sport Coaching Journal, 2024)
The coach-athlete dyad is complex where both parties can often have contrasting perceptions of each other. The purpose of this research was to examine coaching behaviors and perceptions of the coach-athlete relationship across different age grades of rugby football union. Coaches (n = 5) and athletes (n = 78) from three separate rugby union teams (Child, Adolescent, and Adult) had their training sessions (n = 3) analyzed using the Coach Analysis and Intervention System. Athlete perceptions of their coaches` behaviors were measured via the Coaching Behavior Scale for Sport, while coach perceptions of their relationship with their athletes were measured using the Coach-Athlete Relationship Questionnaire. Prescriptive coaching styles were observed in all coaches as Coach Analysis and Intervention System results showed high levels of explicit behaviors: "instruction," "direct management," and "feedback." All coaches utilized similar time proportions within sessions for Coach Analysis and Intervention System "Practice," "Playing," and "Management" states, respectively. Questionnaire results revealed positive perceptions between coaches and athletes for all teams. Despite positive bidirectional relationships, the prescriptive coaching style displayed by all coaches may not align to best coaching practice. Development of a coach`s behaviors, training content, and perceptions through coach education has the potential to enhance their athletes` sporting experience, athletic development, and sport-specific competencies.